Inflation and Unemployment Trade-off in the Global Economy in Indonesia Post COVID-19: Revisiting the Phillips Curve Concept: JEL Classification: E24, E31, E32, E52, O53 - Ayu, Catur Diah; Febiani, Fasya; Ardhani, Furkon; Leonardo, Muhammad; Syahwa, Nabillah; Nuraya, Ahmad Setiawan (Newinera Publisher, 2025)
The purpose of this study is to re-evaluate the relevance of the Philipps curve in Indonesian economy post COVID-19 pandemic. According to the Phillips Curve theory, there is a negative correlation between unemployment and inflation, but the post-pandemic economic landscape presents complications. Using a descriptive perspective, and linear regression on the 2019 − 2024 inflation and unemployment data, research suggests that they are inversely associated with each other, yet, insiginificant from the statistical point of view. So this says that: whatever the causes of inflation, they are mostly from other variables such as changes in global supply chains and international policy decisions (global in addition to domestic policy) rather than unemployment. The traditional view of the Phillips Curve model thus is considered not suitable in modeling Indonesia macroeconomic nowadays. These findings underscore the need for a more flexible, locally-sensitive and data-informed approach to policy-making with respect to the economy.